1995
DOI: 10.1002/jsfa.2740680403
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the composition of various acyl lipids, tocopherols and lignans in sesame seed oils roasted in a microwave oven

Abstract: Seeds from various strains of cultivated Sesamum indicum Linn (colour of seeds: black, brown and white) were exposed to microwave roasting for 16 and 30min at a frequency of 2450MHz and were studied not only for different acyl lipids and their fatty acid compositions, but also for the contribution of antioxidants to the oxidative stability of the oils. Lipids from all-seeded strains were comparable in their total fatty acid composition, with linoleic, oleic, stearic and palmitic acids as the major acids. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 31 publications
(7 reference statements)
10
70
0
Order By: Relevance
“…A slight increase in ligustroside aglycon content and a rising in the formation of oxidized dialdehydic form of elenolic acid linked to tyrosol was observed in the samples heated for 10 minutes. Lignans like 1-acetoxypinoresinol and pinoresinol were not affected by microwave heating, confirming that these compounds are highly stable to microwave heating (Yoshida et al, 1995). The authors concluded that, when compared with frying, microwave heating is a less destructive culinary method regarding the phenol compounds (Brenes et al, 2002 Brenes et al (2002).…”
Section: Phenolic Compoundsmentioning
confidence: 87%
“…A slight increase in ligustroside aglycon content and a rising in the formation of oxidized dialdehydic form of elenolic acid linked to tyrosol was observed in the samples heated for 10 minutes. Lignans like 1-acetoxypinoresinol and pinoresinol were not affected by microwave heating, confirming that these compounds are highly stable to microwave heating (Yoshida et al, 1995). The authors concluded that, when compared with frying, microwave heating is a less destructive culinary method regarding the phenol compounds (Brenes et al, 2002 Brenes et al (2002).…”
Section: Phenolic Compoundsmentioning
confidence: 87%
“…According to FAO data for 2010 [9], sesame seed production occupied 78 million acres, with a production of 3.84 million tons. The sesame seeds contain on average 44 to 58% oil, 18 to 25% crude protein, 13.5% carbohydrates and 5% ash [10][11][12][13]. The sesame seeds oil fatty acid composition is on average 18.5% saturated fatty acids (SFA), 45.4% monounsaturated fatty acids (MUFA), and 36.1% polyunsaturated fatty acids (PUFA), with oleic and linoleic acids being the main components [13].…”
Section: Introductionmentioning
confidence: 99%
“…This food is made up 22-30% protein, thus being an excellent source of energy (564 kcal/100 g); defatted peanut fl our is a byproduct of peanut processing, which contains 47-55% proteins with high nutritional value ( Yu et al, 2007). The main proteins are two globulins, arachine and conarchine, that represent at least 95% of the total seed proteins (Yoshida et al, 1995;Andersen et al,1998;Han et al, 2009). Phytosterols and triterpenes make up the greatest proportion of the unsaponifi able components of vegetable oils (Azadmard-Damirchi et al, 2005); they are considered to have anti-inflammatory, anti-bacterial, antiartherosclerotic, antioxidative (Lagarda et al, 2006), antiulcerative and antitumor properties in humans (Moreau et al, 2002), as well as contributing to the oxidative and thermal stability and shelf-life of vegetable oils (Beveridge et al, 2002;Przybylski andEskin, 2006, Alvarenga andEsteban, 2005).…”
Section: Introductionmentioning
confidence: 99%